1997
DOI: 10.1023/a:1007906413195
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The microorganisms associated with fermented African oil bean (Pentaclethra macrophylla Bentham) seed during ugba production was studied. Only bacteria were isolated from the ugba samples used. Although the bacteria included Bacillus spp., Lactobacillus spp., Staphylococcus spp., Micrococcus spp. and members of the family Enterobacteriaceae, only the Bacillus spp. were found to ferment African oil bean seeds to ugba. Bacillus spp. were the predominant microorganisms present, constituting over 95% of the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Metabolic and enzymatic hydrolysis of Bacillus species serves to break down the protein into amino acids (Isu and Njoku, 1997). Odunfa and Oyewole (1986) and Ghosh et al (2013) observed that all the Bacillus species that have been associated with the fermentation of the oil bean seeds are mainly proteolytic, and 97.3% of these Bacillus species are also lipolytic.…”
Section: Microbiological Changes During Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic and enzymatic hydrolysis of Bacillus species serves to break down the protein into amino acids (Isu and Njoku, 1997). Odunfa and Oyewole (1986) and Ghosh et al (2013) observed that all the Bacillus species that have been associated with the fermentation of the oil bean seeds are mainly proteolytic, and 97.3% of these Bacillus species are also lipolytic.…”
Section: Microbiological Changes During Fermentationmentioning
confidence: 99%
“…Furthermore, because of the stress associated with the food processing, it would be important to use culture dependent and independent methods in order to find/detect non-culturable or not yet cultured microorganisms. Available information in literature shows that organisms such as E. coli, Staphylococcus aureus and other members of the Enterobacteriaceae have been isolated from condiments in West Africa (Isu and Njoku, 1997; Okorie and Olasupo, 2013a). …”
Section: Microbiological Safety Of Fermented African Oil Bean Seedsmentioning
confidence: 99%
“…The isolated Bacillus species are nonpathogenic, saprophytic mesophiles commonly associated with soil, air and water. According to Isu and Njoku (1997), Bacillus species constitute over 95 per cent of the total microbial population density in African oil bean seed fermentation into ugba, a soup condiment. The isolated Bacillus species have been variously identified as playing major parts in the fermentation of other unconventional legumes for the production of condiments (Enujiugha, 2009;Enujiugha and Badejo, 2002;Chinma et al, 2023).…”
Section: Results and Discussion Enumeration Characterization And Isol...mentioning
confidence: 99%